Nilai-Nilai Matematis dalam Budaya Balikpapan: Kajian Etnomatematika - Nur Ismiyati; Besse Intan Permatasari (Lembaga Yasin AlSys, 2026)
Although ethnomathematics studies have been widely conducted on various local cultures in Indonesia, research that specifically discusses the identification of mathematical values in Balikpapan community culture remains limited. This study aims to identify and describe the mathematical values contained in Balikpapan culture through an ethnomathematics study. This study employed a qualitative approach with an exploratory-ethnographic design. The research informants consisted of two resource persons, namely a local cultural activist and an East Kalimantan cultural researcher, who were selected through purposive sampling. Data were collected through semi-structured interviews and cultural documentation and were then analyzed using NVivo-assisted thematic analysis through the stages of data reduction, open coding, axial coding, theme categorization, and data interpretation. The results showed that Balikpapan culture contains various mathematical concepts integrated into community cultural practices, including geometry, transformation, symmetry, measurement, ratio, proportion, repeated patterns, similarity, congruence, and simple statistics. These concepts were found in Balikpapan Batik, Shaho Batik, Rumah Lamin, Kenyah carvings, traditional weaving, and local culinary products such as mantau and amplang. These findings contribute to the development of ethnomathematics studies on multiethnic culture in East Kalimantan and broaden understanding of the relationship between culture and the mathematical activities of society. The conclusion of this study affirms that mathematics develops contextually in community cultural activities and can be used as a meaningful source of mathematics learning. The implications of this study include theoretical contributions to the development of ethnomathematics literature and practical implications for the development of local culture-based mathematics learning.